INFORMATION SECURITY FRAMEWORK INTEGRATING CRYPTOGRAPHY FOR SECURE INTERNET OF THINGS COMMUNICATION - Zainal Syahlan; Khalid Al-Shaibani; Layla Al-Farsi (Yayasan Adra Karima Hubbi, 2026)
The rapid growth of the Internet of Things (IoT) has introduced significant security challenges due to the increasing interconnectivity of devices and the sensitive nature of the data exchanged. Securing IoT communications is crucial to prevent unauthorized access, data breaches, and cyberattacks. However, traditional cryptographic methods often fail to meet the unique needs of IoT systems, which are constrained by resource limitations such as processing power and energy consumption. This research aims to develop a comprehensive information security framework that integrates cryptographic protocols tailored to secure IoT communications while maintaining efficiency. The study employs a mixed-methods approach, combining simulation-based experiments and expert interviews. Various cryptographic techniques, including AES, RSA, and Elliptic Curve Cryptography (ECC), are evaluated in IoT network configurations across different environments. Performance metrics such as encryption time, energy consumption, and data integrity are measured to assess the framework’s effectiveness. The results demonstrate that ECC offers the best balance between security and resource consumption, outperforming AES and RSA in terms of efficiency. Expert feedback confirms the feasibility and scalability of the proposed framework. This research contributes to the field by offering a novel approach to IoT security that can be applied to real-world networks, ensuring secure and efficient communication.